Religião e economia em Antonil - Mendes, Claudinei Magno Magre [UNESP] (My University, 2010)
In our analysis of Antonil, author of Cultura e opulência do Brasil, we oppose to the historiography that analyses him as a writer who examines Brazilian society of the late seventeenth and early eighteenth centuries, sometimes from a religious perspective, others from the economy perspective. Thus, the historiography sometimes explains him as an author who has a religious vision of society, others as an author who would have an economic view of it. In our viewpoint, both ways to consider him fail for being extreme. To comprehend him, it is necessary to understand him from the issues he has dealt with and how he dealt with them. Only then we can reconcile the religious and economic aspects of his worldview.

Em nossa análise de Antonil, autor de Cultura e opulência do Brasil, contrapomonos à historiografia que o analisa como um escritor que examina a sociedade brasileira de finais do século XVII e início do XVIII ora da perspectiva da religião, ora da perspectiva da economia. Assim, a historiografia ora o explica como um autor que possui uma visão religiosa da sociedade, ora como um autor que teria uma visão econômica dela. A nosso ver, ambas as maneiras de considerá-lo pecam por extremar essas concepções. Para se compreendê-lo é necessário entendê-lo a partir das questões que tratou e como as tratou. Somente assim podemos conciliar os aspectos religiosos e econômicos da sua concepção de mundo.
Religion and economics in Antonil
Keywords: Antonil; Religion; Economics; Slavery; Antonil; Religião; Economia; Escravidão